Type 3 Diabetes Mellitus, Insulin Resistance, Alzheimer's Disease and Role of Alpha-Linolenic Acid in Blood-Brain Barrier Repair - Zanwar, Anand A.; Joshi, Asavari A.; Gaikwad, Prajakta S.; Hegde, Mahabaleshwar V. (Chronicle of Diabetes Research and Practice, 2024)
Abstract Alzheimer's disease (AD), is often referred to as Type 3 diabetes mellitus (T3 DM). It has now become evident that T3 DM contributes significantly to the pathogenesis of AD. The T3 DM has a distinct identity being very much selective for blood-brain barrier (BBB) and separated from peripheral diabetes. Alpha-linolenic acid (18:3, ALA) is considered an essential fatty acid that is responsible for the formation of long-chain eicosapentaenoic acid (20:5) and docosahexaenoic acid (22:6, DHA). DHA is an important structural fatty acid of the human brain. The recent literature comes to the conclusion that ALA is an ideal source of DHA. T3 DM can cause, insulin resistance in the brain and impairment in glucose utilization. This has very serious implications on BBB integrity. It has been shown now that ALA very efficiently can provide energy to endothelial cells of the BBB by β-oxidation and facilitate DHA entry to the brain. It has also been shown that some DHA is formed in BBB and some ALA that enters the brain also gets converted to DHA. The role of other players such as Apolipoprotein E protein, Tau and Beta-amyloid, and glycogen synthase kinase are briefly mentioned. The new findings, that the primary event in BBB damage is the pathogenesis of AD, may help in the development of new more effective drugs and treatment modalities.